2021
DOI: 10.1097/sga.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prepackaged Low-Residue Diet on Bowel Preparation for Colonoscopy

Abstract: This meta-analysis aimed to evaluate the impact of prepackaged low-residue diet (PLRD) on bowel preparation for colonoscopy. We searched PubMed, Web of Science, EMBASE, and Cochrane Library databases from inception to August 2020. Randomized controlled trials (RCTs) comparing PLRD with clear liquid diet (CLD) or self-prepared LRD were considered for inclusion. The analysis calculated the odds ratio (OR) for the rate of adequate bowel preparation, patient tolerance, willingness to repeat bowel preparation, tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, inadequate bowel preparation is a common problem in gastroenterological practice worldwide. Inadequate bowel cleansing adversely affects various aspects of the colonoscopy procedure, such as prolonging CIT and reducing ADRs (Alvi et al, 2019; Zhang et al, 2021). Poor preparation quality may also increase the risk of procedural-related complications (e.g., perforation, bleeding), as well as increase healthcare costs and patient discomfort due to the need for reexamination (Hotta, 2022; Murphy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, inadequate bowel preparation is a common problem in gastroenterological practice worldwide. Inadequate bowel cleansing adversely affects various aspects of the colonoscopy procedure, such as prolonging CIT and reducing ADRs (Alvi et al, 2019; Zhang et al, 2021). Poor preparation quality may also increase the risk of procedural-related complications (e.g., perforation, bleeding), as well as increase healthcare costs and patient discomfort due to the need for reexamination (Hotta, 2022; Murphy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate bowel preparation is crucial for a successful colonoscopy. [ 10 11 ] However, chronic constipation has been identified as an important independent risk factor for inadequate bowel preparation. [ 12 13 ] Studies have shown that more than 30% of older patients with constipation experience inadequate bowel preparation, leading to a series of adverse consequences, including higher rates of missed adenomas and failed cecal intubation, extended procedure durations, and increased medical costs.…”
Section: Introductionmentioning
confidence: 99%